Analysis Of Teacher Competency From An Islamic Perspective In The Implementation Of The Independent Curriculum In Vocational Schools - Fadillah, Aisyah Raihan; Fitriyani, Fitriyani; Helandri, Joni; Yunus, Muhammad (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2025)
This research is about the competency of PAI teachers in implementing the independent curriculum. Many teachers still face difficulties in understanding and applying the new concepts promoted by this curriculum. Therefore, the aim of this research is to find out how competent teachers are in implementing the independent curriculum as well as the supporting and inhibiting factors. This research uses field research, with a qualitative approach. Data was collected by observation, interviews and documentation. Then it is analyzed through data collection, data reduction, data presentation and drawing conclusions. In implementing the independent curriculum, teachers use various teacher competencies. For example, pedagogical competence has five roles, namely the ability to understand the character of students, the ability to create learning designs, develop a curriculum, the ability to carry out educational learning and the ability to evaluate learning outcomes. And professional competence has five roles, namely the ability to understand educational principles, the ability to understand teaching materials, compiling teaching programs, implementing programs in the field of education and the ability to evaluate the results of the teaching and learning process. And there are supporting factors such as existing facilities and infrastructure, improving teacher qualifications, innovation in teaching, and support from the school and there are also inhibiting factors, namely, poor time management, differences in student character, and limited references.